The Effectiveness of Guided Inquiry Strategy on Students’ Collaborative Skill - Putri, Fiky Auliyah; Anggraito, Yustinus Ulung; Alimah, Siti (Journal of Biology Education, 2018)
This research aims to analyze collaborative skill through guided inquiry strategy on cell bioprocess material and analyzerelationships of collaborative skill with student's cognitive result. Student’s collaborative skill which assessed were student’s participation in experimental activities, students’s participation in discussion activities, adaptation in grup and flexible work. This research method uses one shot case study with pre-experimental design. The subjects of this study were students of class XI MIPA 1, XI MIPA 2 and XI MIPA 3 with a total of 107 students. The collaborative skill of student’s assessed using observation, self-assessment and peer assessment. Then the results of the assessment were correlated with student cognitive study results. A total of 91.6% of students have excellent collaborative skills and 8.4% of students have good category. The correlation test results showed that there is a positive relationship between collaborative skill and student test result. It can be concluded that guided inquiry strategy is effective toward students collaborative skill and gives positive relationship between collaborative skill and student's cognitive result